Structural DNA Nanotechnology: Growing Along with NanoLetters - Seeman, Nadrian C. (2010)
During the past decade, the field of structural DNA nanotechnology has grown enormously, not only in the number of its participants, but also qualitatively in its capabilities. A number of goals evident in 2001 have been achieved: These include the extension of self-assembled crystalline systems from 2D to 3D and the achievement of 2D algorithmic assembly. A variety of nanoscale walking devices have been developed. A key unanticipated development was the advent of DNA origami, which has vastly expanded the scale of addressable DNA structures. Nanomechanical devices have been incorporated into 2D arrays, and into 2D origami structures, as well, leading to capture systems and to a nanomechanical assembly line. DNA has been used to scaffold non-DNA species, so that one of its key goals has been achieved. Biological replication of DNA nanostructures with simple topologies has also been accomplished. The increase in the number of participants in the enterprise holds great promise for the coming decade.